THE EFFECT OF GAMBIER EXTRACTS (Uncaria gambir [Roxb.]) AS ANTISEPTIC ON GINGIVAL WOUND IN RATS - Siti Rusdiana Puspa Dewi; Anna Pratiwi; Teodorus Teodorus (Odonto : Dental Journal, 2018)
Background: The main principle in treatment of wounds is infection control by using antiseptic. Gambier (Uncaria gambir [Roxb.]) containing catechins and tannins reported that has an antiseptic eﬀect. This aim of this study was to determine the eﬀect of gambier extract as antiseptic on gingival wound in rats.Methods: In vivo study, used pretest-posttest only control group design had been conducted in Animal house, Medical Faculty of Sriwijaya University and Province’s Health Laboratory in Palembang. There were 30 white Wistar rats divided into fve groups. Group 1 was given 10% povidone-iodine ointment (positive control), group 2 was given a placebo ointment (negative control), group 3, 4, and 5 were given an ointment with 10%, 15%, and 20% gambier extracts. Gingival labial wound of the mandible was induced with cylinder diamond bur, then swabbed before and after treatment. Gingival swab samples were cultured in agar medium and incubated for 24 hours. The number of bacterial colonies from all groups were counted by colony counter. The statistical analysis was used IBM SPSS statistics version 22,0.Result: The result showed that the number of bacterial colonies from all groups decreased signifcantly after treatment, except for negative control. The higher concentration of gambier extract led the better eﬀect of antiseptic.Conclusion: It can be concluded that gambier extract has antiseptic eﬀect of gingival wound in rats.